Multifactor dimensionality reduction reveals the effect of interaction between ERAP1 and IFIH1 polymorphisms in psoriasis susceptibility genes - Zhang, Chang; Qin, Qin; Li, Yuanyuan; Zheng, Xiaodong; Chen, Weiwei; Zhen, Qi; Li, Bao; Wang, Wenjun; Sun, Liangdan (Frontiers in Genetics, 2022)
Background: Psoriasis is a common immune-mediated hyperproliferative skin dysfunction with known genetic predisposition. Gene–gene interaction (e.g., between HLA-C and ERAP1) in the psoriasis context has been reported in various populations. As ERAP1 has been recognized as a psoriasis susceptibility gene and plays a critical role in antigen presentation, we performed this study to identify interactions between ERAP1 and other psoriasis susceptibility gene variants. Methods: We validated psoriasis susceptibility gene variants in an independent cohort of 5414 patients with psoriasis and 5556 controls. Multifactor dimensionality reduction (MDR) analysis was performed to identify interaction between variants associated significantly with psoriasis in the validation cohort and ERAP1 variants. Then, we conducted a meta-analysis of those variants with datasets from exome sequencing, target sequencing, and validation analyses and used MDR to identify the best gene–gene interaction model including variants that were significant in the meta-analysis and ERAP1 variants. Results: We found that 19 of the replicated variants were identified with p < 0.05 and detected 6 single nucleotide polymorphisms of psoriasis susceptibility genes in the meta-analysis. MDR analysis revealed that the best predictive model was that between the rs27044 polymorphism of ERAP1 and the rs7590692 polymorphism of IFIH1 [cross-validation consistency = 9/10, test accuracy = 0.53, odds ratio = 1.32 (95% CI, 1.09–1.59), p < 0.01]. Conclusion: Our findings suggest that interaction between ERAP1 and IFIH1 affects the development of psoriasis. This hypothesis needs to be tested in basic biological studies.